Arjé, Life and Movement in the Milesia School - Tomar Romero, Francisca (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2021)
This article is a review of the contributions of the early Milesians presocratic philosophers from their own conceptual framework and beliefs. From this perspective, and trying to identify the interpretations added through the direct and indirect sources of its transmission, we will analyze the relationship between the wet and life in Thales of Miletus, Anaximander's explanation of the origin of life and man, and density as a quantitative and qualitative criterion in Anaximenes.